Dynamic analysis of the evolution of the number of medical specialists in the Spanish Health System. (1st January 2002) - Isabel, Maria; Magdaleno, Alonso
The evolution of the number of medical specialists in the Spanish Health System has been and continues to be determined by various factors. Among them, it is worth pointing out the lack of restrictive policies on the number of entrants into colleges of medicine, as well as the scarcity of studies analysing the profile of physicians required in the future or defining their sphere of professional activity. The imbalance between health professionals entering into and departing from the system has resulted in an increase in the number of physicians in Spain. In this article, we will show a projection of the number of medical specialists, by their specialties, for the years ahead.